Obesity, Inflammation, and Exercise Training: Relative Contribution of iNOS and eNOS in the Modulation of Vascular Function in the Mouse Aorta - Silva, Josiane F.; Correa, Izabella C.; Diniz, Thiago F.; Lima, Paulo M.; Santos, Roger L.; Cortes, Steyner F.; Coimbra, Cândido C.; Lemos, Virginia S. (Frontiers in Physiology, 2016)
Background - The understanding of obsesity-related vascular dysfunction remains controversial mainly because of the diseases associated with vascular injury. Exercise training is known to prevent vascular dysfunction. Using an obesity model without comorbidities, we aimed at investigating the underlying mechanism of vascular dysfunction and how exercise interferes with this process. Methods - High-sugar diet was used to induce obesity in mice. Exercise training was performed 5 days/week. Body weight, energy intake, and adipose tissues were assessed; blood metabolic and hormonal parameters were determined; and serum TNFα was measured. Blood pressure and heart rate were assessed by plethysmography. Changes in aortic isometric tension were recorded on myograph. Western blot was used to analyze protein expression. Nitric oxide (NO) was evaluated using fluorescence microscopy. Antisense oligodeoxynucleotides were used for inducible nitric oxide synthase isoform (iNOS) knockdown. Results - Body weight, fat mass, total cholesterol, low-density lipoprotein cholesterol fraction, insulin, and leptin were higher in the sedentary obese group (SD) than in the sedentary control animals (SS). Exercise training prevented these changes. No difference in glucose tolerance, insulin sensitivity, blood pressure, and heart rate was found. Decreased vascular relaxation and reduced endothelial nitric oxide synthase (eNOS) functioning in the SD group were prevented by exercise. Contractile response to phenylephrine was decreased in the aortas of the wild SD mice, compared with that of the SS group; however, no alteration was noted in the SD iNOS-/- animals. The decreased contractility was endothelium-dependent, and was reverted by iNOS inhibition or iNOS silencing. The aortas from the SD group showed increased basal NO production, serum TNFα, TNF receptor-1, and phospho-IκB. Exercise training attenuated iNOS-dependent reduction in contractile response in high-sugar diet–fed animals, decreased iNOS expression, and increased eNOS expression. Conclusion - Obesity caused endothelium dysfunction, TNFα, and iNOS pathway up-regulation, decreasing vascular contractility in the obese animals. Exercise training was an effective therapy to control iNOS-dependent NO production and to preserve endothelial function in obese individuals.